Security areas for elk during archery and rifle hunting seasons. Issue 5 (31st March 2017) - Ranglack, Dustin H.; Proffitt, Kelly M.; Canfield, Jodie E.; Gude, Justin A.; Rotella, Jay; Garrott, Robert A.
ABSTRACT: Fall elk ( Cervus canadensis ) habitat management on public lands provides security areas for reasonable elk survival and hunter opportunity. The management focus of maintaining or improving security areas, combined with conservative harvest regulations, may explain why some elk populations have increased in the western United States. However, in areas that include lands that restrict public hunter access, elk may alter their space use patterns during the hunting season by increasing use of areas that restrict public hunter access rather than using security areas on adjacent public lands. We used global positioning system location data from 325 adult female elk in 9 southwest Montana populations to determine resource selection during the archery and rifle hunting seasons. We found that during the archery season, in order of decreasing strength of selection, elk selected for areas that restricted access to public hunters, had greater time‐integrated normalized difference vegetation index values, had higher canopy cover, were farther from motorized routes, and had lower hunter effort. During the rifle season, in order of decreasing strength of selection, elk selected for areas that restricted access to public hunters, were farther from motorized routes, had higher canopy cover, and had higher hunter effort. Interactions among several covariates revealed dependencies in elk resource selection patterns. Further, cross‐population analyses revealed increased elk avoidance of motorized routes with increasing hunter effort during both the archery and rifle hunting seasons. We recommend managing for areas with ≥13% canopy cover that are ≥2, 760 m from motorized routes, and identifying and managing for areas of high nutritional resources within these areas to create security areas on public lands during archery season. During the rifle season, we recommend managing for areas with ≥9% canopy cover that are ≥1, 535 m from motorized routes, and are ≥20.23 km 2 . Lastly, given increased elk avoidance of motorized routes with higher hunter effort, we recommend that to maintain elk on public lands, managers consider increasing the amount of security in areas that receive high hunter effort, or hunting seasons that limit hunter effort in areas of high motorized route densities. © 2017 The Authors. Journal of Wildlife Management Published by Wiley Periodicals, Inc. Abstract : We recommend that managers develop areas with ≥13% canopy cover that are ≥2, 760 m from a motorized route during the archery season and for areas ≥20.23 km 2 with ≥9% canopy cover that are ≥1, 535 m from a motorized route during the rifle season to maintain elk distribution on publicly accessible lands. Given the strength of selection for areas that restricted access to public hunters in both seasons, we recommend managers work closely with private landowners to increase public accessibility to private lands if management goals are to reduce elk population size, while also considering the amount of hunter pressure and motorized routes in the elk populations they are managing.